النّقد الاجتماعي في المقامة الأندلسيّة - راشد, ذياب; داؤد, جمانة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
لم يكن كتّاب المقامة الأندلسية بمنأى عن مشاهد الحياة المتنوّعة في مجتمعهم، بل استطاعوا بوساطة إدراكهم الفطن أن ينتقوا من مشكلات واقعهم ما يشاؤون، ويعيدوا تنظيمها في صور فنيّة، في محاولة جادّة منهم لإيجاد الحلول المناسبة لها، وأدركوا بنفاذ بصيرتهم الكيفيّة التي يتفاعلون بها مع واقعهم الملموس حين يريدون تسليط عدسة النقد على ظاهرة من ظواهره، متّخذين من تصوير المفاسد ووصف الحال والشّكوى والتّذمُّر والسّخرية والفكاهة ونموذج المكدي، أدواتٍ تعينهم في التّنفيس عمّا في نفوسهم. يهدف المقال إلى تسليط الضّوء على هذه الأدوات التي اعتمد عليها المقاميّون الأندلسيّون في توجيه سهام نقدهم نحو كلّ ما يسبّب لهم ضغطاً نفسيّاً.ويعتمد المقال المنهج الاجتماعي لتحقيق الهدف المنشود منه. Al-Andalucia Magamat book was not far away from the variety of life scenes intheir society.But,by their intelligent awareness they could select some of their problems and re-organise them in artistic picture,trying seriously to find suitions.they conceived by their deep sight how to react sensibly with their fact,when they wanted to depict a phenomenon.They used certain tools to depict the corruption describing the state,the complaint,the sarcasm,the humour and Al-Makdi type.This study aims to throw thelight on these tools which Al-Makdi writers and the Andalucians used to direct their critical arrows towards all that caused their psychological pressure.This study also depends on descriptionand analysis as a method to achieve this aim.